Mineral Contents of Several Grape Seeds - Musa Ozcan, Mehmet (Asian Journal of Chemistry, 2010)
The mineral contents (Al, B, Ca, Co, Mo, Cr, Fe, K, Mg, Mn, Na, P, S, Se and Zn) of some grape seeds collected from different locations of Turkey were established by inductively coupled plasma atomic emission spectrometry (ICP-AES). Ca, K, Mg, Na and P were established as the major minerals in Dimrit (Doganhisar-Konya), Iri ak Uzum (Doganhisar-Konya), topacik (Konya), Koz (Kargicak-Silifke-Mersin) and Honusu (Gulnar-Mersin) grape seeds, respectively. While Al, B, Fe, Mn and Zn mineral contents of seeds were found partly similar in all the seeds, the Co, Mo, Cr and Se contents were found very low. As a result, grape seeds were thought to be important sources of nutrients and essential elements.